21ST CENTURY SKILLS IN THE CONTEXT OF LIFE QUALITY - Zeide, Inga; Odiņa, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article addresses comparative qualitative content analysis as a part of the grounded theory research to explore the relationship between English language proficiency of economically active adults and their quality of life. Using comparative qualitative content analysis of the policy documents in respect of lifelong learning as main data collection method, the authors of the article aim to identify the relationship between the 21st century skills and indicators of life quality by comparing the sources that define the 21st century skills and analysing them in the context of the “8+1” dimensions of life quality offered by the European Union. The following research questions have been proposed: how 21st century skills are defined in the policy documents and how they relate to the quality of human life. The analysis of European Parliament, Council of the European Union, Word Economic Forum and Eurostat policies, models, strategies and their implementation in respect of lifelong learning reveals existing gaps and points at the urgent need in profiling the development of human skills to enhance human well-being and life quality in Europe. Besides, developing new skills and improving existing ones can be a tool for improving the quality of life in the future, whereas the dimensions of life quality can serve as a prerequisite for skills development.